1952
DOI: 10.1111/j.1365-2621.1952.tb16801.x
|View full text |Cite
|
Sign up to set email alerts
|

SPOILAGE OF CANNED FOODS CAUSED BY THE BACILLUS MACERANS‐POLYMYXA GROUP OF BACTERIA

Abstract: MemDers of the Bacillus maceram-polymyxa group of bacteria have not been included among the major groups of canned food spoilage organisms even though Cameron, Esty, and Williams ( 7 ) proved a related species, B. betmigrificans: to cause "black beets" and other mesophilic members of the genus are well known for their ability to spoil a variety of such foods. .] Nevertheless, since 1943 several outbreaks of canned food spoilage have been observed in which it was possible to incriminate either B. macerans o r B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1954
1954
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…They also ferment purified pectic acid and a-D-galacturonic acid as energy sources j both with copious gas production. I n vitro studies already reported indicate that these bacteria can survive and grow in environments having p H values as low as 3.8 (23,24). The limiting factor would appear to be salt tolerance…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They also ferment purified pectic acid and a-D-galacturonic acid as energy sources j both with copious gas production. I n vitro studies already reported indicate that these bacteria can survive and grow in environments having p H values as low as 3.8 (23,24). The limiting factor would appear to be salt tolerance…”
Section: Discussionmentioning
confidence: 97%
“…which has been reported as less than 10% for the most resistant, trained cultures of these bacteria (24). SUMMARY An attempt was made to determine the sources and types of microorganisms which might be associated with the softening of salt stock cucumbers.…”
mentioning
confidence: 99%
“…As a result, pasteurization processes utilizing temperatures of 85 to 95°C are often adequate for this class of foods. A few publications, however, have indicated that some rare sporeforming strains can grow at a pH of 3.7 or lower, and have been responsible for spoilage of acidified vegetables (9), peaches and pears (10), and wine (3,5).…”
mentioning
confidence: 99%
“…Incidents of gaseous spoilage of canned fruit products by P. macerans, P. polymyxa and B. licheniformis (canned mango pulp) have also been reported (Vaughn et al, 1952;Azizi and Ranganna, 1993). A common spoilage condition of bread, known as 'rope', is caused by growth of Bacillus spp.…”
Section: Foods Spoiled By Aerobic and Facultatively Anaerobic Spore-fmentioning
confidence: 99%